2008
DOI: 10.1128/aem.00386-08
|View full text |Cite
|
Sign up to set email alerts
|

Subfunctionality of Hydride Transferases of the Old Yellow Enzyme Family of Flavoproteins of Pseudomonas putida

Abstract: To investigate potential complementary activities of multiple enzymes belonging to the same family within a single microorganism, we chose a set of Old Yellow Enzyme (OYE) homologs of Pseudomonas putida. The physiological function of these enzymes is not well established; however, an activity associated with OYE family members from different microorganisms is their ability to reduce nitroaromatic compounds. Using an in silico approach, we identified six OYE homologs in P. putida KT2440. Each gene was subcloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Instead, paralogous gene pairs are often subfunctionalized and frequently have overlapping activities that allow both complementation and maintenance of the original functions and an independent evolution of activities. This was recently shown for members of the Old Yellow Enzyme family of flavoproteins, which detoxify nitroaromatic compounds in Pseudomonas putida and other microorganisms (35,36,38).…”
mentioning
confidence: 75%
“…Instead, paralogous gene pairs are often subfunctionalized and frequently have overlapping activities that allow both complementation and maintenance of the original functions and an independent evolution of activities. This was recently shown for members of the Old Yellow Enzyme family of flavoproteins, which detoxify nitroaromatic compounds in Pseudomonas putida and other microorganisms (35,36,38).…”
mentioning
confidence: 75%
“…These include a classical arsenic-responsive ArsR repressor with homology to ArsR of E. coli (PA2277) and three uncharacterized ArsR-family proteins (PAO279, PAO547 and PA4354) (Cai et al, 1998;Stover et al, 2000). The aim of this study was to characterize the novel ArsR-family regulator encoded by PA4354, which appears to be a non-classical ArsR-family regulator, as reflected by the fact that PA4354 is encoded within a putative operon with an uncharacterized major facilitator superfamily (MFS) transporter and the old yellow enzyme (OYE)-family reductase XenB (Pak et al, 2000;van Dillewijn et al, 2008). Previously, we showed that PA4354 is directly regulated by the LysR-type transcriptional regulator MexT (Tian et al, 2009a, b).…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6][7][8] Hence, OYEs represent a group of enzymes with industrial interests. Although many OYE family members have been identified from yeast, bacteria, and plants recently [9][10][11][12][13][14][15][16][17][18] ) and their potential metabolic functions have been suggested, the exact physiological functions of OYEs are largely unknown. 11,[19][20][21] Gluconobacter oxydans is regarded as one of the most important industrial bacteria due to its unique ability to incompletely oxidize a wide range of carbohydrates and alcohols with excellent efficiency and regio-, stereo-, and enantio-selectivity under natural conditions.…”
mentioning
confidence: 99%